Students’ perceptions of school climate as determinants of wellbeing, resilience and identity - Aldridge, Jill; Fraser, Barry; Fozdar, F.; Ala'i, Kate; Earnest, Jaya; Afari, E. (Sage Publications, 2016)
© 2015, © The Author(s) 2015. This study examined the relations between school climate variables and students’ feeling of wellbeing, life satisfaction, ethnic identity, moral identity and resilience. Furthermore, the study also examined the interrelationships between these five outcome variables. Six aspects of the school climate were measured: teacher support, peer connectedness, school connectedness, affirming diversity, rule clarity and reporting and seeking help. The participants included 2202 students, the data from whom included 2122 cases that were complete and usable (1058 boys and 1059 girls) from six public high schools in Perth, Western Australia. These data were analysed by means of structural equation modelling (SEM) analysis. All six school climate factors were related to student wellbeing. These relations were primarily indirect (with the exception of teacher support, school connectedness and affirming diversity which had a direct influence), mediated through the students’ sense of ethnic and moral identity, resilience and life satisfaction.